The Right to Information and Privacy : Balancing Rights and Managing Conflicts - Banisar, David (World Bank, Washington, DC, 2015)
The right to privacy and the right to information are both essential human rights in the modern information society. For the most part, these two rights complement each other in holding governments accountable to individuals. But there is a potential conflict between these rights when there is a demand for access to personal information held by government bodies. Where the two rights overlap, states need to develop mechanisms for identifying core issues to limit conflicts and for balancing the rights. This paper examines legislative and structural means to better define and balance the rights to privacy and information.